Psychoanalysis and the War-Zone: Victor Tausk on WWI - Jukić, Tatjana (2011)
Taking up Victor Tausk's views on the specific conditions of psychoanalysis in WWI, I addressed how this encounter effects a kind of zoning in what both psychoanalysis and the concept itself of a world war entail as a totalizing gesture. While that seems to lessen perhaps the importance of both to our grasp of the twentieth century – specifically where the twentieth century provides a scene of instruction to accessing the biopolitical – my presentation focused on the emancipatory aspects of this encounter and of the zoning it implies.